Managerial Effectiveness and Efficiency of SBI in Himachal Pradesh - Devi, Lata (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2018)
Managerial effectiveness varies from organization to organization and from job to job. The concept of managerial effectiveness is the central issue in management. Managerial effectiveness has to be defined in terms of output rather than input, by what a manager achieves rather than by what he does. Effectiveness is best seen as something a manager produces from a situation by managing it appropriately. It represents output, not input. The manager must think in terms of performance, not personality. It is not so much what a manager does, but what he achieves. The measure of effectiveness whether of an organization or individual is performance that is the attainment of the objective with a style. The study covers managerial effectiveness in SBI in Himachal Pradesh. The various indicators such as appraisal system, training techniques and facilities, career planning, organization development interventions has been considered and analyzed. The study has been analyzed by using simple mathematical tools and chi-square test.